Clinical outcomes of left atrial appendage occlusion versus direct oral anticoagulation in patients with atrial fibrillation and prior ischemic stroke: A propensity-score matched study. (15th September 2022) - Korsholm, Kasper; Valentin, Jan Brink; Damgaard, Dorte; Diener, Hans-Christoph; Camm, Alan John; Landmesser, Ulf; Hildick-Smith, David; Johnsen, Søren Paaske; Nielsen-Kudsk, Jens Erik
Abstract: Background: This propensity-score matched study investigated clinical outcomes associated with left atrial appendage occlusion (LAAO) versus direct oral anticoagulation (DOAC) in patients with AF and prior ischemic stroke. Methods: AF patients enrolled in the Amulet Observational Study with a history of ischemic stroke and successful LAAO ( n  = 299) were compared with a propensity-score matched cohort of incident AF patients with prior ischemic stroke and treated by DOAC ( n  = 301). The control cohort was identified through the Danish National Patient Registries. Propensity score matching was based on covariates of the CHA2 DS2 -VASc and HAS-BLED scores, with a 1:2 ratio and using Greedy 5:1 digit matching with replacement. The analysis included 2-years follow-up, with a primary composite outcome of ischemic stroke, major bleeding (BARC ≥ 3) or all-cause mortality. Results: Mean (SD) CHA2 DS2 -VASc scores were 5.26 (1.42) and 5.40 (1.31) and HAS-BLED scores were 3.95 (0.91) and 4.03 (0.96), for the LAAO and DOAC group, respectively. Total number of primary composite outcome events were 61 (12.4 events/100 patient-years) and 117 (26.9 events/100 patient-years) in the LAAO and DOAC group, respectively. Risk of the primary composite outcome was significantly lower in the LAAO group, hazard rate ratio [HR] 0.48 (95% CI: 0.35–0.65). Ischemic stroke risk was comparable, HR 0.71 (95% CI: 0.34–1.45), while risk of major bleeding, HR 0.41 (95% CI: 0.25–0.67), and all-cause mortality, HR 0.48 (95% CI: 0.32–0.71), were significantly lower with LAAO. Cardiovascular mortality did not differ statistically between the LAAO and DOAC group, HR 0.75 (95% CI: 0.39–1.42). Results were consistent across sensitivity analyses. Conclusion: This study indicated significantly lower risk of the composite outcome of stroke, major bleeding and all-cause mortality with LAAO therapy compared to DOAC, in patients with AF and prior stroke. The stroke prevention effectiveness appeared similar, with a significantly lower risk of major bleeding events with LAAO. The suggested clinical benefit of LAAO over DOAC require confirmation in the ongoing randomized OCCLUSION-AF trial. Highlights: Patients with atrial fibrillation and prior ischemic are at particularly high risk of stroke recurrence and bleeding. LAAO has shown promise in randomized studies, yet, data is sparse and absent in AF patients with prior stroke. RRRisk of the composite outcome of stroke, major bleeding, and mortality was significantly lower with LAAO compared to DOAC. The stroke prevention effectiveness appeared similar, with significantly lower risk of major bleeding with LAAO. These results demand confirmation in the ongoing randomized OCCLUSION-AF trial (NCT03642509 )